Identification of study habits and skills associated with the academic performance of Bachelor's degree Food Science and Technology students at the University of León (Spain). Issue 4 (29th August 2020) - Renes, E.; Prieto, B.; López, M.; Fresno, J. M.; González‐Raurich, M.; Tornadijo, M. E.; Prieto, M.; Álvarez‐Ordóñez, A.
Abstract: The aim of this study was to identify factors that influence the academic success or failure of Food Science and Technology students at the University of León (Spain). A questionnaire of 68 questions was distributed among 185 students during the 2017 to 2018 academic year. Those students who were satisfied with passing exams, studied in the library, and/or faced personal problems showed low academic performance. In addition, some factors, such as studying Physics previously, attending class, and/or studying all the topics for the exams, were associated ( P < 0.05) positively with the grade point average obtained. Academic performance of the students in the different years of study did not present significant differences ( P ≥ 0.05). This study reinforces the need to introduce changes in the current University of León´s education program.